DEVELOPMENT DIRECTIONS OF COOPERATION BASED ON INDUSTRIAL CLUSTERS (Web of Teachers: Inderscience Research, 2024)
The article highlights the issue of how the development of production clusters that process local raw materials is one of the ways to mobilize resources to increase economic growth in the regions.